Young customers' perception towards Facebook as a social networking site : an empirical study of Filipino consumers - Azizah Endatun Talusan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
The ability of social networking site (SNS) to reach a greater range of audience instantly poses a challenge nowadays. Also, several technological advances resulted to changes in the behavior of consumers particularly their perception towards Facebook as SNS. Thus, this research sought to analyse the perception of young Filipinos towards Facebook as social networking site subjects from the viewpoints of young Filipinos in the city of Cotabato, Southern Philippine. The primary focus of this research is to address the applicability of extended TAM. This model should enable pertinent parties to obtain a better understanding about young Filipino customers' perception and able to help online business to promote their goods and services through Facebook. The aim of this study is to know whether the variables of extended TAM affect the young Filipino customers' perception positively or not. Based on the study conducted, a total of 200 young respondents mostly are students (84 males and 116 females) were drawn from a stratified sample randomly. The questionnaire was adopted from four previous studies using 5 Likert scale. Throughout the 4 variables of young Filipino customers' perception towards Facebook as SNS investigated in this study, only 3 were significantly positive. In this research, it asserts that perceived ease of use (PEOU), perceived usefulness (PU) and trust propensity (TP) are positively correlated to customers perception towards Facebook. Furthermore, perceived risk is negatively correlated to customers' perception with regards to Facebook as SNS. This study found that perceived ease of use (PEOU), perceived usefulness (PU) and trust propensity (TP) influence the young Filipino perception. The findings indicate that young Filipino customers purchase goods and services carefully through SNS particularly from Facebook. The results show that the extended TAM structure directly impacts the three variables PEOU, PU and TP contexts. In conclusion, the results show the success of the proposed extension of TAM in achieving the objectives of this research.